Knowlton Circles: A Later Neolithic and Early Bronze Age Ceremonial Complex and Its Environs—A Review. (3rd July 2017) - Gale, John
ABSTRACT: The larger henge monuments of Wessex have been the focus of detailed archaeological investigation for over a century and consequently their study has provided a greater, albeit fragmentary, understanding of later Neolithic society. For the most part such studies have continued to show that these great mega-structures of the third millennium B.C. persist as beacons of ceremonial functionality into which later societies invested much of themselves, intellectually, spiritually and unquestionably physically. While Stonehenge, Avebury and Durrington Walls continue to attract a great deal of attention with ongoing research, comparable sites in Dorset have been less well researched. Two campaigns of archaeological investigation undertaken in the Allen Valley of east Dorset by the author have focussed upon the complex of earthworks at Knowlton and additionally at one of three broadly contemporary barrow cemeteries located nearby. The findings from these investigations are beginning to shed more light on the possible origins and development of these important but weakly understood landscapes. This paper outlines some of the main findings from these investigations and posits a chronological framework for the integration of a group of monuments that formed both a ceremonial landscape and a geographical and spiritual home for communities that lasted for a thousand years. GRAPHICAL ABSTRACT: